Ethnic Entrepreneurs (translation by M. Dobryakova) - Roger Waldinger; Howard E. Aldrich; Robin Ward (Journal of Economic Sociology, 2010)
During recent years there has been a surge of studies of entrepreneurs from different ethnic minorities. Ethnic minoritieshave different resources and face different opportunities than mainstream entrepreneurs.